Die belydenis van die kerk - Buitendag, J. (Acta Theologica, 2002)
The article contends that the doctrine of the church should rather be seen as telling something about the church than about the Bible. Different doctrines are thus the result and not the source of theology. And because a creed is functioning like a language, it constitutes and profiles a church’s self-understanding. The presupposition of all this is that God has revealed Himself in Jesus Christ. Scripture is therefore primarily not revelation as such, but testimony of the revelation in Christ. The article ends with the three major Afrikaans-speaking reformed churches’ official declarations on their views regarding the relationship between Scripture and doctrine. The author concludes that a slight trace of what George Lindbeck calls “propositionalism” is present in these respective views. The article is dedicated to Prof. P. C. Potgieter, a much-honoured colleague among systematic theologians and church leaders here and abroad. Dogmatics has always been for him church dogmatics, and thus the relevance of doctrine.